Tipping the Scales: Effects of Gender, Rape Myth Acceptance, and Anti-Fat Attitudes on Judgments of Sexual Coercion Scenarios - Zidenberg, Alexandra M. (Journal of interpersonal violence, 2021)
A damaging belief exists that to become a victim of sexual violence, victims must be deemed sexually desirable. As a result, sexual violations where the victims are individuals whom society may deem as less attractive—such as overweight women—may elicit less empathy for the victim or minimize the likelihood they are believed. Yet, there is some evidence that overweight women actually report higher rates of sexual violence than women of other weight categories. Although there has been some research implicating weight biases in sexual assault cases, this has not been extended to cases of sexual coercion despite their growing share of police reports. A sample of 168 participants were recruited from Canada via social media (n = 82) and through a midsized university in Ontario, Canada (n = 86). Using a mock jury paradigm, participants responded to a vignette depicting the sexual coercion of a thin or overweight woman. Participants reported their opinions on the sexual coercion scenario, and prejudicial attitudes, using two standardized scales. Men reported greater rape myth acceptance, anti-fat attitudes, and victim responsibility and endorsed significantly more perpetrator mitigating factors and expressed more negative affect toward the victim. Participants in the overweight condition also expressed greater perpetrator sympathy, greater perpetrator mitigation, and less negative affect toward the perpetrator. These results suggest that overweight women may face additional barriers when reporting their experiences of sexual coercion, particularly to men.